The Clinical Features, Pathogenesis and Methotrexate Therapy of Chronic Chikungunya Arthritis - J. Kennedy Amaral; Peter C. Taylor; Mauro Martins Teixeira; Thomas E. “Tem” Morrison; Robert T. Schoen (Viruses, 2019)
Chikungunya fever (CHIKF) is an emerging viral infection that has spread widely, along with its Aedes vectors, throughout the tropics and beyond, causing explosive epidemics of acute illness and persistent disabling arthritis. The rheumatic symptoms associated with chikungunya virus (CHIKV) infection include polyarthralgia, polyarthritis, morning stiffness, joint edema, and erythema. Chronic CHIK arthritis (CCA) often causes severe pain and associated disability. The pathogenesis of CCA is not well understood. Proposed hypotheses include the persistence of a low level of replicating virus in the joints, the persistence of viral RNA in the synovium, and the induction of autoimmunity. In this review, we describe the main hypotheses of CCA pathogenesis, some of which support methotrexate (MTX) treatment which has been shown to be effective in preliminary studies in CCA.